Ward based goal directed fluid therapy (GDFT) in acute pancreatitis (GAP) trial: A feasibility randomised controlled trial. (August 2022) - Froghi, Farid; Soggiu, Fiammetta; Ricciardi, Federico; Vindrola-Padros, Cecilia; Floros, Lefteris; Martin, Daniel; Filipe, Helder; Varcada, Massimo; Gurusamy, Kurinchi; Bhattacharya, Satya; Fanshawe, Angela; Delcea, Bogdan; et al.
Abstract: Background: Goal-directed fluid therapy (GDFT) reduces complications in patients undergoing major general surgery. There are no reports of cardiac output evaluation being used to optimise the fluid administration for patients with acute pancreatitis (AP) in a general surgery ward. Method: 50 patients with AP were randomised to either ward-based GDFT (n = 25) with intravenous (IV) fluids administered based on stroke volume optimisation protocol or standard care (SC) (n = 25), but with blinded cardiac output evaluation, for 48-h following hospital admission. Primary outcome was feasibility. Results: 50 of 116 eligible patients (43.1%) were recruited over 20 months demonstrating feasibility. 36 (72%) completed the 48-h of GDFT; 10 (20%) discharged within 48-h and 4 withdrawals (3 GDFT, 1 SC). Baseline characteristics were similar with only 3 participants having severe disease (6%, 1 GDFT, 2 SC). Similar volumes of IV fluids were administered in both groups (GDFT 5465 (1839) ml, SC 5211 (1745) ml). GDFT group had a lower heart rate, blood pressure and respiratory rate and improved oxygen saturations. GDFT was not associated with any harms. There was no evidence of difference in complications of AP (GDFT 24%, SC 32%) or in the duration of stay in intensive care (GDFT 0 (0), SC 0.7 (3) days). Length of hospital stay was 5 (2.9) days in GDFT and 6.3 (7.6) in SC groups. Conclusion: Ward-based GDFT is feasible and shows a signal of possible efficacy in AP in this early-stage study. A larger multi-site RCT is required to confirm clinical and cost effectiveness. Highlights: The GAP trial was the first ward-based, non-invasive cardiac output monitoring (NICOM) guided fluid therapy trial in acute pancreatitis. Delivering NICOM-guided goal-directed fluid therapy (GDFT) on the ward was both safe and feasible. There is some signal of modulating end-organ function and reduction of progression to severe disease. This study provides the evidence basis for a larger multi-centre randomised trial of clinical and cost-effectiveness.